Non-conventional Drainage of Waterlogged Low-lands through Recharge Wells - Patra, S K; Ray, R; Ghosh, R K (Journal of Agricultural Engineering, 2001)
The coastal saline land of Barachouka basin in Midnapore district and the inland lowlying land of Dankuni basin in Hooghly district in West Bengal are seriously affected by flat to concave topography, heavy and deep textured soils, high congestion of rainfall and runoff, intrusion of saline sea or river water and non-functioning drainage outlets. Under this situation, adoption of conventional surface and sub-surface drainage measures are infeasible. An attempt was, therefore, made to dispose of the surface accumulated runoff into deeper layers of the aquifer through recharge wells viz. strainer type tubewell and cavity well with a view to restoring the normal cultivation environment by reducing the submergence damage to paddy plants. The studies revealed that the steady state recharge rate through strainer type tubewell in coastal Barachouka basin was 1.378 Ips and through cavity well in inland Dankuni basin was 0.6371 Ips, respectively. Superimposing the cumulative recharge over the time distribution of the magnitude of paddy plant submergence, it was calculated that one strainer type tubewell per two hectares of land in Barachouka basin and two cavity wells for every hectare of land in Dankuni basin would be sufficient enough to reduce the drainage congestion and submergence damage to paddy plants to safe limit. These two non-conventional approaches of drainage, in spite of some limitations, were observed to be techno-economically feasible for reclamation of hitherto uncultivated low-lying lands prone to severe salinity and / or waterlogging hazards, for sustainable paddy production.